Genesis of southern Podolya’s flora (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Florogenetic analysis showed that the studied flora had started forming since last glacial period with being completely migratory. The two types of relicts – the Valday and Atlantic ones – are established. On the base of synergetic theory the irregularity of specification in time was proved on the different taxonomic levels.
Keywords: flora, relict, Podolia.